Some notes on the literature on socio-economic change in Southeast Asia - Mustapha Jar. (Universiti Kebangsaan Malaysia, 1977)
The literature on socio-economic change is extremely large, and is spread over several branches of social sciences. This article a sample of the literature on socio-economic change in Southeast Asia. Mainly, the literature can be labeled as follows: works on change under colonial situation; works on applied anthropology or directed change; works on the responsiveness of peasant farmers; works that show the mutual interaction of economic, political and cultural forces; works on the effects of modernizing activities upon traditional society and economy.